ERROR ANALYSIS IN USING SIMPLE PAST IN NARRATIVE PARAGRAPH AT STIKOM BALI - I Gusti Agung Vony Purnama (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2018)
ABSTRACT This study aims to find out the error of the students in writing a narrative essay and to find out the factor that causing the errors. The students under concern were the second-semester students of academic year 2016 taking the English 2 subject at STIKOM Bali Dual-Degree Program. This study used the theory of Writing particularly Narrative Writing, and theory of Error Analysis. The theory of Writing was used to measure the students’ ability in making a narrative writing. The theory of Error Analysis was used to find out the students’ types of error, and also to find out their source of error. The result of this study showed that the highest error was the error of misformation with the percentage 70.45% and made by 13 students. The lowest error was the error of addition with the percentage 11.36% and made by 4 students. The error of omission was 18.18% and made by 7 students. From those result, it can be concluded that the source of the students’ error in narrative writing was caused by the intralingual interference since they were very confuse in using the type of sentence in their target language particularly in using simple past. It is hoped that this study can help teacher in preparing the materials to be easier understood by the students and help them improving their ability in narrative writing. Keywords: narrative writing, error analysis.